Capacity of Local Institutions in Good Governance Implementation at the Local Context: The Case of Sleman Regency, Indonesia - Bagus Wahyu Hartono (Iapa Proceedings Conference, 2019)
The implementation of good governance at the village level is an essential element in shaping good governance at the district level. The practices that have been carried out at the village level are considered to be a reflection of what governance has originated from. In the midst of the implementation of decentralization policies, village communities are an integral part of the political dynamics in Indonesia. Villages with various local institutions have an essential role in managing local issues. In this research, data is mainly analyzed through a qualitative approach. Some quantitative analysis through scoring and descriptive statistical techniques are also conducted. Data collection methods are used as follows: documentation, observation, surveys with questionnaires, in-depth interviews, and Focus Group Discussion (FGD). This research identifies the Village Government has sufficient capacity to carry out its duties in village development. However, the realization of its capacity to solve local problems is still limited and only a partial solution. Weak coordination between institutions and limited budgets is the main problem found in study sites that hinders capacity realization in solving local problems. Furthermore, local government has made little effort to develop rural institutional capacity. So far, it only emphasizes capacity building for village officials, while other institutions only get little attention from the local government.